2017 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--28606
|View full text |Cite
|
Sign up to set email alerts
|

Laying the Foundations of a Learning Platform for Humanitarian Engineering: Methodological Approach and Results

Abstract: He is part of the Enhancing Student Experience team and, in this role, is tasked to work with the engineering, architecture, and IT faculty to enhance learning and teaching in classroom and across programs. He earned his PhD at Purdue University in Engineering Education and also has a M.S. in Aeronautical and Astronautical Engineering. His research interests include Humanitarian Engineering, social justice in engineering education, global engineering education, professional engineering practice, and curriculum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Research in HE education has, in fact, mostly focused on the development of HE curricula (e.g., Smith et al, ) or on evaluating how HE courses help students develop technical and professional skills (e.g., Litchfield, Javernick‐Will, & Maul, ). A recent scoping review showed that most studies have used only self‐report Likert scales to assess key competencies (Mazzurco & Murzi, ), which are useful in evaluating students' self‐concept and confidence but limited in determining whether they have actually acquired such skills. Therefore, there are still many opportunities to further investigate the development of key attributes relevant to HE practice, especially including socio‐technical thinking.…”
Section: Introductionmentioning
confidence: 99%
“…Research in HE education has, in fact, mostly focused on the development of HE curricula (e.g., Smith et al, ) or on evaluating how HE courses help students develop technical and professional skills (e.g., Litchfield, Javernick‐Will, & Maul, ). A recent scoping review showed that most studies have used only self‐report Likert scales to assess key competencies (Mazzurco & Murzi, ), which are useful in evaluating students' self‐concept and confidence but limited in determining whether they have actually acquired such skills. Therefore, there are still many opportunities to further investigate the development of key attributes relevant to HE practice, especially including socio‐technical thinking.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, after further iterations, we looked for commonalities amongst the themes and merged them to obtain our framework of five guiding principles. This process also led us to develop an initial classification of design methods, as presented in more detail in related publications (Mazzurco, 2016;Mazzurco & Jesiek, 2017).…”
Section: Qualitative Content Analysismentioning
confidence: 99%
“…To address this gap, we have undertaken a research project with three main goals: 1) identifying principles that can enable meaningful community participation, 2) classifying design methods that allow community members to influence engineered solutions, and 3) investigating the experiences of humanitarian engineers to provide lessons learned and real-life examples of their partnerships with community members (Mazzurco, 2016;Mazzurco & Jesiek, 2017). This paper reports results from the first phase of the research project that aimed to create a framework of principles by integrating findings from the extant HE literature.…”
mentioning
confidence: 99%